Impact of dental implant insertion method on the peri-implant bone tissue: Experimental study - Stamatović Novak; Matić Smiljana; Tatić Zoran; Petković-Ćurčin Aleksandra; Vojvodić Danilo; Rakić Mia (Vojnosanitetski Pregled)
Background/Aim. The function of dental implants depends on their stability in bone tissue over extended period of time, i.e. on osseointegration. The process through which osseointegration is achieved depends on several factors, surgical insertion method being one of them. The aim of this study was to histopathologically compare the impact of the surgical method of implant insertion on the peri-implant bone tissue. Methods. The experiment was performed on 9 dogs. Eight weeks following the extraction of lower premolars implants were inserted using the one-stage method on the right mandibular side and two-stage method on the left side. Three months after implantation the animals were sacrificed. Three distinct regions of bone tissue were histopathologically analyzed, the results were scored and compared. Results. In the specimens of one-stage implants increased amount of collagen fibers was found in 5 specimens where tissue necrosis was also observed. Only moderate osteoblastic activity was found in 3 sections. The analysis of bone-to-implant contact region revealed statistically significantly better results regarding the amount of collagen tissue fibers for the implants inserted in the two-stage method (Wa = 59 < 66,5, α = 0.05), but necrosis was found in all specimens, and no osteoblastic activity. Histopathological analysis of bone-implant interface of one-stage implants revealed increased amount of collagen fibers in all specimens, moderate osteoblastic activity and neovascularization in 2 specimens. No inflammation was observed. The analysis of two-stage implants revealed a marked increase of collagen fibers in 5 specimens, inflammation and bone necrosis were found in only one specimen. There were no statistically significant differences between the two methods regarding bone-implant interface region. Histopathological analysis of bone tissue adjacent to the one-stage implant revealed moderate increase of collagen tissue in only 1 specimen, moderate increase of osteoblasts and osteocytes in 3 specimens. No necrotic tissue was found. The analyzed specimens of bone adjacent to two-stage implants revealed a moderate increase in the number of osteocytes in 3 and a marked increase in 6 specimens respectively. This difference was statistically significant (Wb = 106.5 > 105, α = 0.05). No necrosis and osteoblastic activity were observed. Conclusion. Better results were achieved by the two-stage method in bone-to-implant contact region regarding the amount of collagen tissue, while the results were identical regarding the osteoblastic activity and bone tissue necrosis. There was no difference between the methods in the bone-implant interface region. In the bone tissue adjacent to the implant the results were identical regarding the amount of collagen tissue, osteoblastic reaction and bone tissue necrosis, while better results were achieved by the two-stage method regarding the number of osteocytes.